Hazard identification, Risk Assessment and Risk Control (HIRARC) on laboratory waste disposal in chemistry laboratory / Nor Aimi Abdul Wahab, Farah Nabilah Ahmad Rahiza and Norain Isa - Abdul Wahab, Nor Aimi; Nabilah, Farah; Isa, Norain (UiTM Cawangan Negeri Sembilan, 2022)
The academic laboratory used for teaching and learning often generates many types of hazardous wastes. It is crucial to have proper laboratory waste disposal management to enhance safety and minimize the environmental effect in the academic laboratory. The objective of this study was to determine the risk associated with waste disposal activity in the chemistry laboratory of Universiti Teknologi MARA Cawangan Pulau Pinang based on the Hazard Identification, Risk Assessment and Risk Control (HIRARC) model. Five chemistry laboratories have been selected for this study. The first step involved hazard identification conducted through workplace inspections and observation. Each hazard was assessed, and the risk was calculated based on the likelihood of occurrence and severity of harm. Several risk control options to reduce or eliminate the risk were proposed. The HIRARC model identified thirty critical hazards in the waste disposal process, with 63.3% classified as low risk and the remaining 33.3% and 3.3% as medium risk and high risk, respectively. Therefore, the waste disposal process can be deemed hazardous to laboratory personnel. The main hazards were chemical (63%), physical (17%), ergonomic (13%), and biological (7%). The high-risk activities were associated with the chemical hazard. Engineering control, administrative control, and personal protective equipment (PPE) are among the control measures presented in this study. The control measures and corrective actions could be applied to improve the safety aspect in the laboratory and prevent accidents.